(untitled) (Revista científica Olimpia, 2019)
The present research work was oriented to the development of an interactive blogs in the sports schools of the province Granma, the same tried to provide a constant interaction between high performance athletes, coaches and teachers with the medical-psychological staff of the Provincial Center of Medicine of Sports in Granma (CEPROMEDE). The research idea arose because the athletes mainly have doubts, issues and aspects that they wish to discuss or clarify with the professionals who attend them, but because of fear, pity or other reasons they do not come close to clarify them and then unfortunate situations that could be avoided. Interactive Blogs is a new way of learning, with a practical future vision where they consult by specialists. The research was of projective type framed in a comprehensive level, with a mixed source design, applied on the current enrollment of schools and academies. The methodologies used were Requirements Engineering and Extreme Programming (XP), allowing the efficient obtaining of the requirements based on a thorough analysis of the environment under study and the active incorporation of medical personnel as main entities of the interaction, as well as the use Unified Modeling Language (UML) allowed to graphically represent the solutions, having as final result a first operative version of the blog adjusting to the existing needs.